2013
DOI: 10.18093/0869-0189-2013-0-1-32-37
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of GSTP1 and EPHX1 genes in smokers and patients with chronic obstructive pulmonary disease stages I and II

Abstract: Polymorphism of GSTP1 and EPHX1 genes in smokers and patients with chronic obstructive pulmonary disease stages I and II SummaryChronic obstructive pulmonary disease (COPD) is known as a disease associated with smoking. Investigation of genetic control of the connective tissue seems to be important. Polymorphism of glutathiontransferase GSTP1 and microsomal epoxidhydrolase EPHX1 genes has been studied in 40 healthy smokers and 40 patients with I and II stages COPD. Analysis of polymorphic loci of GSTP1 and EPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…72 Nevzorova et al showed that deletion polymorphism of GSTT1 is recommended to use as a marker for predictive diagnostics of development and progress of COPD. 73 76 The combination of GSTM1 null, GSTT1 null and GSTP1 Val/Val was shown to be associated with the maximal increased risk (12-fold) of COPD. 37 The combined GSTT1 and GSTM1 deficiency is associated with an accelerated age-related decline of lung function in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Nevzorova et al showed that deletion polymorphism of GSTT1 is recommended to use as a marker for predictive diagnostics of development and progress of COPD. 73 76 The combination of GSTM1 null, GSTT1 null and GSTP1 Val/Val was shown to be associated with the maximal increased risk (12-fold) of COPD. 37 The combined GSTT1 and GSTM1 deficiency is associated with an accelerated age-related decline of lung function in males.…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of Asians, 40% of Africans and 20% of Caucasians show GSTT1 enzyme deficiency . Nevzorova et al showed that deletion polymorphism of GSTT1 is recommended to use as a marker for predictive diagnostics of development and progress of COPD . Kukkonen et al detected a modifying effect of GSTT1 gene polymorphism in the individual risk and severity of emphysematous changes …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a decrease in the frequency of the dominant S allele of the same polymorphism was found, especially in patients with GOLD III and IV stage COPD classification. 19,20,30 As a percentage of healthy persons, the distribution of the SS-Ss-ss genotypes was 92.1% -7.9% -0%, and in COPD patients, respectively: 29.3% -40.3% -30.4%. There was no homozygosity of the S allele in patients with COPD IV by GOLD.…”
Section: Discussionmentioning
confidence: 93%
“…Some experiments describe development of endothelial dysfunction of cerebral and conductance arteries in mice exposed to tobacco smoke that was characterized by significant intensification and predominance of constricting activity of arteries, as well as abnormal reduction of cerebral arterial vasodilatory reserve along with asymmetric increase of carotid artery constriction [11,14]. Apart from endothelial dysfunction and alterations of vasomotor reactions in response to tobacco smoking, some experiments revealed a connection between long-term exposure to tobacco smoke and irreversible changes in large arteries, such as wall thickening and deterioration of their mechanical properties [24,25]. At the same time, smoke-exposed rats showed elevated levels of elastase and progressing degenerative changes of thoracic and abdominal aorta accompanied by a lower quality of their elastic and mechanical properties [26].…”
Section: Effect Of Tobacco Smoke Components On Vascular Functionmentioning
confidence: 99%